Contributions of cognitive sciences and affectivity in interaction with autistic children: pedagogical considerations (Research, Society and Development, 2022)
In this work, we will discuss how the care of the autistic subject happens and if it takes into account the functioning of the cognition of knowledge of this individual since the way the brain works implies its intellectual development, thus, we will reflect on the potential contribution of the neurosciences for educational practices aimed at children with Autism Spectrum Disorder (ASD), as supported by cognitive sciences, professionals who work with the child (teachers, therapists, others), as well as the family themselves, will be able to better understand the process of her learning. For that, we are theoretically based on authors such as Cosenza, Silva, Fonseca, Wallon, Piaget, Souza who explain about the cognitive sciences, neuroplasticity, neuropsychology, learning and affectivity. In the methodology, a qualitative approach was used, of a bibliographic nature of the field research type, having as an instrument of data collection online questionnaires with closed and open questions. From the data analysis, it was concluded that knowledge in the area of cognitive sciences can be used as a favorable resource for the intellectual and social development of the child with ASD, as well as affectivity, since affection is able to promote balance between cognitive structures and may even promote the development of new structures to solve some difficulties presented by children and promote learning.